O pacto pela gestão e a saude na fronteira : condições e relações de trabalho do assistente social em debate - Silva, Maria Geusina da (2013)
This study proposes to examine the effects of the implementation of the pact by management in labor relations and conditions of social workers in health in the border region of Foz do Iguaçu and Ciudad del Est Brazil and Paraguay, as these phenomena affect or impact the illness professional and professional responses. The research design includes an intense revisiting the databases of different research projects of diversified research centers affiliated to CNPq, in its various lines of concentration, also incorporates field work to rescue some data and information management specifically Shaft trabalho.Parte is indicative that the implementation of the pact by management in twin city boundary line to not focus on labor management plastered the possibilities of change, innovation and repoliticisation SUS, showing adoption of the precepts of the reform of state formulated in 90.Compreende decade that the Pact for Health to enable a new bias reorganization of federal pacts, through decentralization, management and with it the allocation of financial resources associated with the proposed relaxation of the rule on behalf of flexible accumulation requires large amounts of changes in labor relations initially and subsequently in terms of achieving this. The indicative of this proposal rests on the centrality of labor management in SUS as the only possible and viable path to realization of the principles and values of the Brazilian health reform.